Rancang Bangun dan Basis Data pada Klinik 24 Jam Secara Konseptual dan Logikal - Wihendro, Wihendro; Indrajani, Indrajani; Capri, Safan (Bina Nusantara University, 2013)
The aim of this research is to design a database model which is conceptual and logical for a 24-hour clinic. The methods used in this research are the data collection through literature studies, surveys, and interviews to the clinic management to get a description of the business processes implemented at a 24-hour clinic. Then we use the conceptual database design method which identifies important entities, relationships entities, and existing attributes. After that, we create a database logical model which represents the clinical database 24 hours. From that, the model is expected to be a logical database model for further development into a clinical application 24 hours to improve the health services to the public.